Kritik Maqashid Syariah terhadap Penyelesaian Nasabah Wanprestasi pada Perbankan Syariah - Munandir, Rahman; Syufaat, Syufaat (Alhamra Jurnal Studi Islam, 2023)
Islamic banks were born for the benefit of humans, not only in this world but also for the happiness of the hereafter. Transactions at Islamic banks are oriented toward the margin, profit sharing, and rent, in contrast to conventional banks whose profit base is based on interest. However, in practice, the settlement of Sharia bank customer defaults is the same as conventional banks, in which the settlement focuses on the sale or auction of guarantees to get funds back from customers. Is this practice in accordance with the objectives of Islamic banks? For that, the author uses maqashid sharia to get the answer.